Impact of complement C3 levels on the development of healthcare-associated infections in intensive care patients: a retrospective case-control study - Chenjuan Wang; Binhao Chen; Zhekai Ying; Mengyuan Shen; Yiling Luo; Tianchen Lin; Dandan Feng; Dongdong Yang; Zhongheng Zhang; Jiannong Wu (Annals of Medicine)
Purpose The immune system serves as a critical line of defence against pathogenic microorganisms. To investigate the impact of immune markers, measured within the first 48 h of intensive care unit (ICU) admission, on the incidence of healthcare-associated infections (HAIs) in ICU patients.Methods This case-control study included 364 patients admitted from 1 January 2020 to 30 November 2023, receiving immune marker testing within 48 h of ICU admission. Cox proportional hazard models and propensity score matching evaluated immune markers’ association with HAIs risk. Log-rank tests compared time-to-event by C3 levels. All data processing and analysis were performed using R version 4.2.0 (R Foundation for Statistical Computing, Vienna, Austria) and Python version 3.11 (Python Software Foundation, Wilmington, DE).Results In total, 258 patients without HAIs (mean [SD] age, 67.24 [17.79] years) and 106 patients with HAIs (mean [SD] age, 73.80 [14.93] years) were included in the final analysis. The HAIs group had older age, longer hospital stay, lower Sequential Organ Failure Assessment (SOFA) scores, and a higher rate of comorbid infections than the non-HAIs group. Also, the HAIs group had a higher proportion of basophils, lymphocytes, monocytes and T suppressor cells (CD3 + CD8+), while the proportion of neutrophils and B cells (CD19+) was lower. After Cox regression analysis and propensity score adjustment, we found that C3 complement levels (HR: 0.40; 95%CI, 0.16–0.98; p = .044) influenced the incidence of HAIs. Patients were then divided into high C3 and low C3 groups based on a cut-off value of 0.455 for C3. A time-to-event plot showed that the median time to HAIs occurrence was nine days in the high C3 group and six days in the low C3 group (p = .048).Conclusions Elevated complement C3 levels may associat with a reduced incidence of HAIs in ICU patients.